2006
DOI: 10.1667/rr3579.1
|View full text |Cite
|
Sign up to set email alerts
|

LET-Dependent Survival of Irradiated Normal Human Fibroblasts and Their Descendents

Abstract: Evidence has accumulated showing that ionizing radiations persistently perturb genomic stability and induce delayed reproductive death in the progeny of survivors; however, the linear energy transfer (LET) dependence of these inductions has not been fully characterized. We have investigated the cell killing effectiveness of gamma rays (0.2 keV/microm) and six different beams of heavy-ion particles with LETs ranging from 16.2 to 1610 keV/microm in normal human fibroblasts. First, irradiated confluent density-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 54 publications
4
58
0
Order By: Relevance
“…Irradiation with carbon ions used in this study is expected to be most effective for cell killing, as it has been shown for human and rodent cells that RBE peaks at 100-200 keV/µm [1,3,8,22]. Carbon-ion irradiation significantly decreased the clonogenicity of FeT-J cells compared to γ-rays, as shown in Fig.…”
Section: Resultsmentioning
confidence: 69%
See 4 more Smart Citations
“…Irradiation with carbon ions used in this study is expected to be most effective for cell killing, as it has been shown for human and rodent cells that RBE peaks at 100-200 keV/µm [1,3,8,22]. Carbon-ion irradiation significantly decreased the clonogenicity of FeT-J cells compared to γ-rays, as shown in Fig.…”
Section: Resultsmentioning
confidence: 69%
“…Irradiation with energetic carbon ions (114 keV/µm), of which LET has been known to maximize biological effects in human and rodent cells [1,3,8,22], exacerbated the killing of feline Tlymphocyte FeT-J cells with RBE of 2.98 relative to the D 10 dose of g-rays (0.2 keV/µm). Inactivation cross-section in cells exposed to carbon ions was 1691-fold higher than that in γ-irradiated cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations